IMPLEMENTASI KEBIJAKAN SINODE GEREJA MASEHI INJILI DI MINAHASA PADA KELOMPOK PELAYANAN LANSIA - Lahindo, Bebi Triwati Natalia Christi; Areros, Wiliam A.; Lotulung, Leviane J.H. (AGRI-SOSIOEKONOMI, 2022)
This research aims to identify and to describe the implementation of the policies of the Evangelical Church synod in Minahasa in the elderly service group. This research was conducted at the GMIM Synod Office, Talete Dua, Central Tomohon District, Tomohon City, North Sulawesi. The research method used in this study is a qualitative research method with a phenomenological approach. The data used are primary data obtained directly from informants and secondary data obtained indirectly. Data were collected through interviews, observation and documentation. The results showed that the Policy Implementation of the GMIM Synod Elderly empowerment service group had implemented several programs that accommodated the elderly in terms of improving relationships, social support as well as aspects of a sense of security, and self-confidence for the elderly in their old age. The obstacles related to the policy of the GMIM Synod Elderly service group management is the unavailability of a managerial center for the empowerment of the elderly in particular, in which there are facilities and infrastructure and a management structure that does not yet have a synodal structural equality level, which causes sometimes the existing programs doesn’t run optimally.